Kinetic and Thermodynamic Study of Oxidative Decolourisation of a Typical Food Dye (Tartrazine) in an Aqueous Environment - F.O. Okeola; E.O. Odebunmi; M.A. Amoloye; H.F. Babamale; S. Thema; J.O. Abdulsalam (Journal of Applied Sciences and Environmental Management, 2020)
The study was carried out to describe the kinetics and thermodynamics of hydrogen peroxide oxidation of a typical food dye (Tartrazine). The effect of different operational factors were investigated spectrophotometricallyat wavelength460 nm under pseudo first order reaction.These included concentration of the oxidant and the dye, the pH, ionic strength and temperature of the reacting medium and the presence of transition metal ion as homogenous catalyst. A complete and smooth decolourisation was observed. The results showed that the rate of oxidation of dye increased with increasing in concentration of substrate and oxidant. Increasing in temperature, ionic strength and pH of the basic reaction medium also raised the reaction rate. The rate of oxidation also increased with increasing in the concentration of Fe (III) ion. Pseudo second order rate constant (k2) obtained was 1.95 x 10-3 M-1s-1 and 3.8 x10-3M-1s-1 in the absence and presence of Fe (III) ion respectively. The Arrhenius activation energy for the oxidation in the absence and presence of Fe (III) ion were 47.23 kJmol-1 and 42kJmol-1 respectively. Other thermodynamic parameters showed entropy of activation (ΔS#), free energy of activation (ΔG#) and Enthalpy of activation of the reaction (ΔH#) in the presence of Fe (III) as -34.7  JK-1mol-1, 48.4 kJmol-1 and 40.30 kJmol-1 respectively. The results in the absence of Fe (III) ion were -24.6 JK-1mol-1, 51.2 kJmol-1 and 44.0 kJmol-1 respectively. The relative lower activation energy (Ea),fairly higher negative value of (ΔS#) and higher (ΔG#) , with higher rate constant in the presence of Fe(III) ion showed Fe(III) ion enhancement of rate of decolourisation.